Peran Pemerintah Desa Dalam Meningkatkan Karakter Peduli Lingkungan Pesisir Pada Masyarakat Desa Pulau Kerumputan - Irmasari Irmasari; Wardiani Hiliadi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study examines the village government's programs and roles in strengthening environmental care character among coastal communities in Pulau Kerumputan Village, Pulau Laut Kepulauan District, Kotabaru Regency. Using a qualitative case study approach, data were collected through observation, in-depth interviews with seven informants (Village Head, Head of the Village Consultative Body, neighborhood unit head, and community members), and documentation, then analyzed via data reduction, display, and conclusion drawing, with validity ensured through extended observation, triangulation, and member checking. Results show the program is realized through the weekly